The Impact of Electronic Records Management on Job Performance and Organizational Effectiveness in Public Service: A Systematic Review and Research Gap Analysis - Rouna Meisda Paoki; Jimmy Herawan Moedjahedy (Jurnal Bisnis dan Komunikasi Digital, 2026)
Effective records management is considered a fundamental component of the administrative structure of public sector organizations. This study aims to examine the shift from traditional paper-based systems to the implementation of Electronic Records Management Systems (ERMS) and its direct effect on employee productivity in the public administration domain. The research aims to present a thorough analysis of the existing empirical research concerning the effectiveness of ERMS implementation in the public administration domain and to highlight the existing research gaps in the relevant scientific community. This study is conducted as a systematic literature review, which is based on the PRISMA 2020 guidelines. The study aims to present the results of the analysis of quantitative empirical research articles retrieved from the most prominent global academic databases, with the search results being relevant to the study period between 2016 and 2026. The results indicate the existence of a statistically significant positive correlation between the implementation of ERMS and employee productivity dimensions such as the speed of task completion, administrative accuracy, and decision-making proficiency. High performance expectancy and perceived usefulness are considered the primary motivating factors of ERMS implementation, as supported by the Technology Acceptance Model (TAM). However, the results indicate the existence of significant barriers to the implementation of ERMS, such as organizational resistance to the implementation of ERMS and the provision of adequate technological training to the workforce. Moreover, the results indicate the existence of critical research gaps concerning the ERMS implementation domain. Thus, these research gaps reveal a relatively limited focus with respect to longitudinal research designs, as well as sub-national administrative units, in developing country contexts. The study concludes that an electronic records management system (ERMS) has the potential to serve as a strategic enabler of efficiency, with the achievement of digital transformation depending on human factors, including management support and employee acceptance.